STRUGGLING FOR THE RIGHT TO REMEMBER: THE INTERNATIONAL CRIMINAL TRIBUNAL FOR THE FORMER YUGOSLAVIA (ICTY) AND THE COMMEMORATION OF GENOCIDE IN PRIJEDOR - JOHANNA PAUL (Washington University Global Studies Law Review, 2020)
The large-scale atrocities committed in the Prijedor municipality of Bosnia-Herzegovina in 1992 have featured prominently in the ICTY’s development—from its establishment, its first trial (Duško Tadić), to its final verdict (Ratko Mladić). As a result, the ITCY has produced a lasting historical record of crimes committed in Prijedor and significantly contributed to the shrinking of the space for their denial, but it did not qualify these crimes as genocide. This article addresses civil society activities aimed toward facing the past and memorialization in Prijedor and the question of how the ICTY has influenced the bottom-up mobilization of survivors and returnees for the right to remember civilian victims in an unfavorable environment. Inspired by previous work on the ICTY’s indirect influence on democratization by sparking civil society activism, I review events in 2012, the 20th anniversary of the heinous war crimes in Prijedor, and analyze how the court has influenced the mobilization of activists locally and abroad and how these activists have sought to influence the court’s work. To discuss this bi-directionality, I first consider how two important ICTY cases—those concerning Radovan Karadžić and Ratko Mladić, both of whom were indicted for genocide in Prijedor and other municipalities in 1992—encouraged the activists to mobilize and demand from local authorities a process of confronting the recent past, and gave legitimacy to the activists’ decision to use the word ‘genocide’ in public commemorations. Second, I address how concentration camp survivors addressed the Tribunal in an on-going process by filing an amici curiae request following a Trial Chamber decision to drop the count under which Karadžić was indicted for genocide in Prijedor and other Bosnian municipalities. The analysis shows how the ICTY has influenced the bottom-up mobilization of survivors and returnees for the right to remember in an unfavorable environment and the lasting impact of that year on local memory politics.
Keywords: ICTY; GENOCIDE